Euler sums are dealing usually with either the harmonic sum or the alternating harmonic sum. Most of the operations and result are, however, similar in many respects.

Hence I propose here to study applications of a unified harmonic sum defined as

$$U(\sigma,n,p) = \sum_{k=1}^n \frac{\sigma^k}{k^p}\tag{1}$$

Here we have introduced a parameter $\sigma$ which for specific values gives back the well known harmonic sums

$$H_{n,p} = U(\sigma = +1, n,p)\tag{2a}$$ $$A_{n,p}= - \overline{H}_{n,p} = U(\sigma = -1,n,p)\tag{2b}$$

Some typical problems to be solved are

1) provide an integral representation of $U(\sigma,n,p)$ analogous to $$H_n = \int_0^1 \frac{1-x^n}{1-x}\,dx\tag{3}$$

2) provide an infinite sum representation of $U(\sigma,n,p)$ analogous to $$H_n = \sum_{m=1}^{\infty}\left(\frac{1}{m}-\frac{1}{m+n}\right)\tag{4}$$

3) Calculate the generating function of order $q$ of $U$ defined as

$$g(\sigma,p,q,z) =g_{p,q}(\sigma,z) = \sum_{n=1}^\infty \frac{z^n}{n^q} U(\sigma, n,p)\tag{5}$$

that is, provide a representation as an integral and as a sum (as in 1), and 2)), and calculate the g.f. for some small values of $p$ and $q$, specifically $p=1$, $q=0,1,2,3(?)$


First we derive the formulas, afterwards we study some applications of these.

1) Integral representation of the unified harmonic sum

$$U(\sigma ,n,p)=U_{n,p}(\sigma)=\sum _{k=1}^n \frac{\sigma ^k}{k^p} \\ =\sum _{k=1}^n \sigma ^k \left(\frac{1}{\Gamma (p)}\int _0^{\infty }t^{p-1}\exp \left(-k t\right)\,dt\right) \\ =\frac{1}{\Gamma (p)}\int _0^{\infty }t^{p-1}\left(\sum _{k=1}^n \sigma ^k \exp \left(-k t\right)\right)\,dt $$ hence

$$U(\sigma ,n,p)=U_{n,p}(\sigma)=\frac{1}{\Gamma (p)}\int_0^{\infty } t^{p-1}\sigma e^{-t}\frac{ 1-\left(\sigma e^{-t}\right)^n}{1-\sigma e^{-t}} \, dt\tag{s1}$$

After the transformation $t\to \log(\frac{1}{x})$ this form of the integral is obtained

$$U(\sigma ,n,p)=U_{n,p}(\sigma)=\frac{\sigma }{\Gamma (p)} \int_0^1 \log ^{p-1}\left(\frac{1}{x}\right)\frac{1-(\sigma x)^n}{1-\sigma x} \, dx\tag{s1a}$$

For $p=1$ this simplifies to

$$U(\sigma,n) = \sum _{k=1}^n \frac{\sigma ^k}{k}=\sigma \int_0^1 \frac{1-(\sigma x)^n}{1-\sigma x} \, dx=\int_0^{\sigma} \frac{1-y^n}{1-y} \, dy\tag{s1b}$$

Here we have abbreviated $U(\sigma,n,p=1) = U(\sigma,n)$.

2) Representation of the unified harmonic sum as an infinite sum

A power series expansion of the denominator in $(s1)$ gives

$$U(\sigma ,n,p)=U_{n,p}(\sigma)=\frac{1}{\Gamma (p)}\int_0^{\infty } t^{p-1}\sigma e^{-t}\frac{ 1-\left(\sigma e^{-t}\right)^n}{1-\sigma e^{-t}} \, dt \\ = \frac{1}{\Gamma (p)} \int_0^{\infty } t^{p-1} \left( 1-\left(\sigma e^{-t}\right)^n\right) \sum_{m=1}^{\infty}(\sigma e^{-t})^m \, dt \\ = \frac{1}{\Gamma (p)}\sum_{m=1}^{\infty} \int_0^{\infty } t^{p-1} \left( 1-\left(\sigma e^{-t}\right)^n\right) (\sigma e^{-t})^m \, dt \\ = \frac{1}{\Gamma (p)}\sum_{m=1}^{\infty} \int_0^{\infty } \left( t^{p-1}(\sigma e^{-t})^m - t^{p-1}\left(\sigma e^{-t}\right)^{m+n}\right)\, dt $$

The two integrals can be easily done so that we get

$$U(\sigma ,n,p)=U_{n,p}(\sigma)= \sum _{m=1}^{\infty } \left(\frac{\sigma ^m}{m^p}-\frac{\sigma ^{m+n}}{(m+n)^p}\right)\tag{s2}$$

Notice that this relation can also be written in terms of standard functions as

$$U(\sigma,n,p)= \operatorname{Li}_p(\sigma )-\sigma ^{n+1} \Phi (\sigma ,p,n+1)\tag{s2a}$$

where $\operatorname{Li}_p(z)=\sum_{k=1}^{\infty}\frac{z^k}{k^p} $ is the polylog function and $\Phi (z ,p,c)= \sum_{k=0}^{\infty}\frac{z^k}{(k+c)^p}$ is the Lerch phi function.

3) The generating function of the unified harmonic sum

The generating function of order $q$ is defined as

$$g_{p,q}(\sigma,z )=\sum_{n=1}^{\infty} \frac{z^n}{n^q}U_{n,p}(\sigma)$$

Inserting $U$ from ${s1}$ we have

$$g_{p,q}(\sigma,z )= =\sum_{n=1}^{\infty} \frac{z^n}{n^q}\left(\frac{1}{\Gamma (p)}\int_0^{\infty } t^{p-1}\sigma e^{-t}\frac{ 1-\left(\sigma e^{-t}\right)^n}{1-\sigma e^{-t}}\right) \, dt \\ =\frac{1}{\Gamma (p)}\int_0^{\infty } t^{p-1}\sigma e^{-t}\frac{1}{1-\sigma e^{-t}}\sum_{n=1}^{\infty} \frac{z^n}{n^q}\left( 1-\left(\sigma e^{-t}\right)^n\right) \, dt $$

The sums can be expressed by polylog functions defined as

$$\operatorname{Li}_{q}(z)=\sum_{n=1}^{\infty} \frac{z^n}{n^q} $$

so that we get finally

$$g_{p,q}(\sigma,z )=\frac{1}{\Gamma (p)}\int_0^{\infty } t^{p-1}(\sigma e^{-t})\frac{ \operatorname{Li}_q(z)-\operatorname{Li}_q\left(e^{-t} z \sigma \right)}{1-\sigma e^{-t} } \, dt\tag{s3}$$

We can get a simplified version doing the integral of the first term giving

$$g_{p,q}(\sigma,z )= \operatorname{Li}_p(\sigma ) \operatorname{Li}_q(z)-\frac{1}{\Gamma (p)}\int_0^{\infty } \frac{t^{p-1} \left(\sigma e^{-t}\right) \operatorname{Li}_q\left(e^{-t} z \sigma \right)}{1-\sigma e^{-t}} \, dt\tag{s4}$$

An alternative representation as a double integral can be obtained replacing $\frac{1}{n^q}$ with an integral, resulting in

$$g_{p,q}(\sigma,z )=\frac{1}{\Gamma (p) \Gamma (q)}\int_0^\infty \int_0^\infty\,ds\,dt \frac{ t^{p-1} s^{q-1} e^{-t-s} (\sigma z) }{ \left(1-e^{-s} z\right) \left(1-\sigma z e^{-s-t}\right)}\tag{s5}$$

If we now do the $t$-integral we get a simpler alternative to $(s3)$

$$g_{p,q}(\sigma,z )= \frac{1}{\Gamma(q)} \int_0^\infty s^{q-1} \frac{\operatorname{Li}_p\left(e^{-s} z \sigma \right)}{1-e^{-s} z}\,ds\tag{s6}$$

4) Micellaneous

The following symmetry relations for even an odd indices hold

$$U_{2n,p}(\sigma) = - U_{2n,p}(-\sigma) +U_{n,p}(\sigma^2) \tag{s4.1}$$ $$U_{2n+1,p}(\sigma) = - U_{2n+1,p}(-\sigma) +U_{n,p}\sigma^2)\tag{s4.2} $$

For $\sigma = 1$ these reduce to

$$H_{2n,p} = \overline{H}_{2n,p} +H_{n,p} \tag{s4.1a}$$ $$H_{2n+1,p} = \overline{H}_{2n+1,p} +H_{n,p}\tag{s4.2b} $$

By repeated partial integration of ${(s1b)}$ we can easily derive the following asymptotic expansion valid for $\sigma \ne 1$

$$U(\sigma,n) = \sigma \int_0^1 \frac{1-(\sigma x)^n}{1-\sigma x} \, dx \overset{n\to\infty} \simeq -\log (1-\sigma ) \\-\sigma ^{n+1} \left(\frac{1}{n (1-\sigma )}-\frac{1}{n^2 (1-\sigma )^2}+\frac{\sigma +1}{n^3 (1-\sigma )^3} \\ -\frac{\sigma ^2+4 \sigma +1}{n^4 (1-\sigma )^4}+\frac{\sigma ^3+11 \sigma ^2+11 \sigma +1}{n^5 (1-\sigma)^5}+O(\frac{1}{n^6})\right)\tag{s4.3}$$

Notice that for $\sigma = 1$ the terms with $\frac{1}{n^3}$ and $\frac{1}{n^5}$ vanish and we recover the asymptotics of $(-\overline{H}_n)$ provided here How to prove the asymptotic expansion $\overline{H}_n \sim \log(2) -(-1)^n\left (\frac{1}{2n}-\frac{1}{4 n^2} +\frac{1}{8n^4}\mp\ldots\right)$?

Recently I became aware of a paper of 2004 https://www.sciencedirect.com/science/article/pii/S0022247X04003920?via%3Dihub (quoted in https://en.wikipedia.org/wiki/Lerch_zeta_function#Asymptotic_expansion) which provided the following expression for the asymptotics of the Lerch Psi function

$$\Phi(z,s,a) \underset{a->\infty} \simeq \frac{1}{1-z} \frac{1}{a^s} + \sum_{k=1}^{N}\frac{ (-1)^k}{k!} \operatorname{Li}_{-k}(z) \frac{(s)_k}{a^{k+s}}+R\tag{s4.4}$$

Using this result the asymptotics of the unified harmonic sum becomes

$$U(\sigma,n) \overset{n\to \infty}\simeq -\log (1-\sigma ) -\sigma ^n \left(\sum _{k=0}^{N} \frac{(-1)^r \operatorname{Li}_{-k}(\sigma )}{n^{k+1}}\right)+O(n^{-N-2})\tag{s4.4a}$$

Notice that the polylog of negative integer index is a quotient of two polynomials. The first few are

$$\left\{\frac{\sigma }{(1-\sigma )},\frac{\sigma }{(1-\sigma )^2},\frac{\sigma ^2+\sigma }{(1-\sigma )^3},\frac{\sigma ^3+4 \sigma ^2+\sigma }{(1-\sigma )^4}\right\}$$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.